Comparative Study Of Iron Sucrose Versus Ferric Carboxymaltose In The Management Of Iron Deficiency Anaemia In Pregnant Women - Dr Mansi Chaudhary (Cuestiones de Fisioterapia, 2025)
Objectives: Iron deficiency anemia is the most common hematological but manageable health problemencountered among the pregnant women globally but more common in developing countries like India.Methods: It is interventional prospective comparative study conducted in Department of Obstetrics andGynaecology at Santosh Medical College over a period of 9 months from September 2023- April 2024. 100pregnant patients with hemoglobin in the range 7 gm/dl - 9 gm/dl between 16 to 34 weeks gestation wereselected randomly. Patients were divided into two groups 50 each. Group 1 is Iron Sucrose (IS) group- patientswere treated with intravenous iron sucrose in multiple doses on alternate days on 0,2,4,6 and 8, 200mg perday, total of 1000mg. Group 2 is Ferric